2005
DOI: 10.1590/s1517-83822005000100013
|View full text |Cite
|
Sign up to set email alerts
|

Pectinase and polygalacturonase production by a thermophilic Aspergillus fumigatus isolated from decomposting orange peels

Abstract: A thermophilic fungal strain producing both pectinase and polygalacturonase was isolated after primary screening of 120 different isolates. The fungus was identified as Aspergillus fumigatus Fres. MTCC 4163. Using solid-state cultivation, the optimum levels of variables for pectinase and polygalacturonase (PG) production were determined. Maximal levels of enzyme activities were achieved upon growing the culture in a medium containing wheat bran, sucrose, yeast extract and (NH4)2SO4 after 2-3 days of incubation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
64
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(77 citation statements)
references
References 24 publications
9
64
0
1
Order By: Relevance
“…Namasivavam et al (2011) working on B. cereus isolated from market solid waste reported that pectinase production was enhanced by wheat bran. Also, Phutela et al (2005) reported the enhancement of pectinase by wheat bran and industrial pectin on the production of pectinase from thermophilic Aspergilus fumigatus isolated from decomposing orange peels. In our study, optimum temperature between 50 and 60°C was obtained for the three Bacillus spp, with B. stearothermophilus showing highest activity at 60°C while B. cereus and B. subtilis both showed highest activities of pectinase at 50°C.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Namasivavam et al (2011) working on B. cereus isolated from market solid waste reported that pectinase production was enhanced by wheat bran. Also, Phutela et al (2005) reported the enhancement of pectinase by wheat bran and industrial pectin on the production of pectinase from thermophilic Aspergilus fumigatus isolated from decomposing orange peels. In our study, optimum temperature between 50 and 60°C was obtained for the three Bacillus spp, with B. stearothermophilus showing highest activity at 60°C while B. cereus and B. subtilis both showed highest activities of pectinase at 50°C.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, 35°C was reported for pectinase from Penicillin chrysogenum (Banu et al, 2010). Phutela et al (2005) reported an optimum temperature of 60°C for thermophilus A. fumigatus pectinase. Other thermophilic fungi have been reported to optimally produce enzymes at 50°C (Rubinder et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Biotechnol., 7 (1): 13-22, 2015 (1%, w/v) as the sole source of carbon and screened for pectinolytic activity by a modified plate method of Phutela et al (2005). The sterilized and cooled medium (pH 6.5) was supplemented with norfloxacin at 300 mg/100 mL before pouring.…”
Section: Screening Of Fungal Isolates For Pectinase Activitymentioning
confidence: 99%
“…For being a saprophytic fungus, important to nutrient recycling, this fungus has already been isolated from different environments such as soil, compost and agricultural waste composting (Straatsma et al, 1994;Latgé, 2001;Phutela et al, 2005).…”
Section: Introductionmentioning
confidence: 99%